Social Media Disorder, Mental Health, and Validation of the Chinese Version of 27-Item Social Media Disorder Scale in Chinese College Students - Lei, Hui; Huang, Yaqing; Chai, Ya; Zhang, Xiaocui (Frontiers in Public Health, 2022)
Objective With the widespread use of social media, excessive use of social media may lead to problematic behaviors such as social media disorder, which has a negative impact on teenagers' mental health. Thus, it is an urgent need to provide a measurement tool to assess social media addiction in different cultures. The aim of this study was to assess the psychometric properties of the Chinese version of 27-item Social Media Disorder (SMD) Scale (developed using the diagnostic criteria of DSM-V Internet Gaming Disorder) in college students, and to verify its impact on mental health. Methods Two online surveys were conducted among a total of 1,539 Chinese college students, including 1,316 subjects in sample 1 and 223 subjects in sample 2. The discrimination, criterion validity, construct validity and reliability of the Chinese version of SMD-27 scale were examined. Results The Chinese version of SMD-27 scale showed excellent psychometric properties. The item-total correlation coefficients of the scale ranged from 0.31 to 0.56, and the item-dimension correlations of the scale ranged from 0.459 to 0.834. Findings from confirmatory factor analysis indicated a great fit of the model of the Chinese version of SMD-27, with CFI = 0.956, TLI = 0.951, RMSEA = 0.036 in sample one and CFI = 0.970, TLI = 0.967, RMSEA = 0.040 in sample two, thus confirming the second-order factor structure of the scale. The SMD-27 scale showed good internal consistency between two different samples with their respective Cronbach's alpha of 0.87 and 0.92, and good test-retest reliability over a period of 1 month. In addition, multiple regression results generally supported the impact of social media addiction on mental health. Conclusion This study provides evidence that the Chinese version of SMD-27 scale is applicable to Chinese college populations, and it is a promising tool for the study of social media addiction in China.